SLC7A11 as a Gateway of Metabolic Perturbation and Ferroptosis Vulnerability in Cancer - Jaewang Lee; Jong-Lyel Roh (MDPI AG, 2022)
SLC7A11 is a cell transmembrane protein composing the light chain of system xc−, transporting extracellular cystine into cells for cysteine production and GSH biosynthesis. SLC7A11 is a critical gateway for redox homeostasis by maintaining the cellular levels of GSH that counter cellular oxidative stress and suppress ferroptosis. SLC7A11 is overexpressed in various human cancers and regulates tumor development, proliferation, metastasis, microenvironment, and treatment resistance. Upregulation of SLC7A11 in cancers is needed to adapt to high oxidative stress microenvironments and maintain cellular redox homeostasis. High basal ROS levels and SLC7A11 dependences in cancer cells render them vulnerable to further oxidative stress. Therefore, cyst(e)ine depletion may be an effective new strategy for cancer treatment. However, the effectiveness of the SLC7A11 inhibitors or cyst(e)inase has been established in many preclinical studies but has not reached the stage of clinical trials for cancer patients. A better understanding of cysteine and SLC7A11 functions regulating and interacting with redox-active proteins and their substrates could be a promising strategy for cancer treatment. Therefore, this review intends to understand the role of cysteine in antioxidant and redox signaling, the regulators of cysteine bioavailability in cancer, the role of SLC7A11 linking cysteine redox signaling in cancer metabolism and targeting SLC7A11 for novel cancer therapeutics.